The transfer of travel habits from childhood to adulthood - Lazar, Anja (Academica turistica, 2017)
This study examines whether tourists' travel habits and patterns transfer from their childhood to adulthood and which elements of their vacation are most commonly repeated in their adulthood. We have examined this phenomenon through a sur- vey questionnaire which has been completed by 111 respondents who take vacations regularly. The survey presented two sets of eleven pairing statements relating to the following travel elements: destination, spatial repetition, frequency, duration, tim- ing, organization, travel party composition, type of vacation, vacation activities, ac- commodation and travel mode. First set of eleven pairing statements referred to the presentwhilethesecondsetreferredtothepast.Wehaveexaminedrepetitionbycal- culating correlations between pairing statements. The results have shown existence of weak correlations between the majority of pairing statements which suggests rep- etition of repetition of childhood patterns and habits. The highest repetition rate has been noted with transport, activities and time elements, while no correlation has been noted with frequency element.
Keywords: navade; potovanja; tourism; turisti; turizem; vzorci